Promoting student engagement: insights from Iceland, Lithuania, and Norway - Petronienė, Saulė; Juzelėnienė, Saulutė; Tautkevičienė, Gintarė; Eyjólfsdóttir, Emma Björg; Stebbins, Randi Whitney; Dovidonytė, Rasa (Frontiers in Education, 2024)
The complex phenomenon of engagement in the research draws upon the sociocultural theories (Kahu, 2013; Kahu &Nelson, 2018) and emphasizes the three interrelated dimensions: behavioral, emotional/affective, and cognitive (Fredricks, 2015). Student engagement in academic life is a key factor for student wellbeing, making it essential to address the issues related to student engagement to be able to foster overall academic success. The research has shown that the COVID-19 pandemic impacted the academic environment including students' performance and their social and private lives. In order to help young people prepare to become students, an analysis of student needs and experiences was carried out at three universities: the University of Stavanger (Norway), Kaunas University of Technology (Lithuania) and the University of Iceland (Iceland). Focus group discussions were used to collect data about the students' experience entering university and what challenges first-year students faced before and during the COVID-19 pandemic. A total of 17 first-year (6 males and 11 females) who started their studies during COVID19 lockdown and 16 second-year students (9 males and 7 females) who started theirs studies before COVID19 participated in the focus groups discussions. The collected data consists of students' responses during the focus group discussions. The qualitative thematic content analysis was used to identify emergent themes and categories. The results of the research indicate that students face several challenges when entering university: adapting to the academic environment and the student role, information overload, social relationships, communication, and self-esteem issues. Students who started their studies during the pandemic indicated different experiences and challenges in adapting to university life. This research faced several constraints, including the limited sample size, the focus on only three universities in Northern Europe, and the reliance on self-reported data from the focus group interviews, which may not fully capture the diversity of student experiences. Despite these limitations, the research provides valuable insights into the impact of the COVID-19 pandemic on student engagement and the unique challenges faced by new students during this period.